Job Placement Assessment–Based Profile and Trends of Vocational High School Students in an Industrial Urban Area: Evidence from Tangerang City (2022–2025) - Mohamad Abdilah Nuradhi; Wikan Putri Larasati; Mokhtar Kusuma Atmaja (International Journal of Science and Environment (IJSE), 2026)
The transition of Vocational High School (SMK) graduates into the labor market represents a critical issue at the intersection of workforce policy and career development, particularly in industrial urban regions. This study examines job placement matching patterns among SMK students in Tangerang City over the 2022–2025 period using secondary data derived from the Job Placement Assessment implemented as part of Indonesia’s national labor policy. The assessment measures psychological readiness across seven dimensions—spirituality, social bonding, diversity orientation, communication style, skill type, global capacity, and business capacity—and generates recommendations for domestic employment, overseas employment, and entrepreneurship. Employing a quantitative descriptive design with a temporal trend perspective, this study analyzes aggregated assessment recommendation patterns to identify stability and change in job placement recommendations within an industrial urban labor market context. The findings reveal a high degree of stability across all seven psychological readiness dimensions throughout the observation period, indicating that vocational students’ core psychological profiles are shaped by long-term cultural and educational processes and remain relatively constant over time. In contrast to this psychological stability, job placement recommendation patterns exhibit a consistent structural pattern rather than dynamic shifts. Recommendations for domestic employment remain dominant across all years, reflecting the strong absorption capacity of Tangerang City’s industrial labor market. At the same time, entrepreneurship recommendations show a gradual increase, suggesting career diversification within a formal employment-oriented context, while overseas employment remains a marginal pathway. These findings indicate that job placement recommendation patterns in industrial urban areas are primarily shaped by regional labor market structures rather than by changes in individual psychological readiness. The study underscores the importance of region-specific interpretation of assessment results and highlights the value of integrating psychological assessment data with urban workforce planning and adaptive career counseling in vocational education settings.